(untitled) (Brazilian Journal of Radiation Sciences, 2018)
The objective of this work was to determine the kinetic parameters of BeO thermoluminescent (TL) samples. The knowledge of the kinetic parameters is important for the general description of the physical characteristics of a thermoluminescent material. Using a linear heating rate of 5K/s-1, the BeO peak temperatures obtained were (474.7 ± 1.2) K and (620.5 ± 1.2) K, respectively, for the first and second TL peaks. The peak shape and the glow curve area measurement methods and the Urbach formula have been used for the trap parameter determination. A kinetic order of about two was determined for the first peak, whereas the second peak followed the first-order kinetics according to the geometrical factor. The energy activation values obtained using different kinds of measurements are in good agreement, including the Kitis method for deconvolution of the glow curve. Furthermore, the results agree with those presented by other authors.